Teaching literature and language through multimodal texts - Domínguez Romero, Elena 1977-; Bobkina, Jelena 1970-; Stefanova, Svetlana 1964- (A volume in the Advances in linguistics and communication studies (ALCS) book series, 2019)
"This book applies multiple language teaching modalities for the teaching of language through literature in the context of primary, secondary and higher education. It offers insight on the impact of such practice on learners with the intention to inspire other teachers to reconsider their own teaching practices"--